(untitled) (Al-Qamar, 2020)
Pakistan is an Islamic country where people from all occupations follow the preaching’s of Islam. This study, "Impact of mediated dress culture on Islamic and social practices of people,” investigates that dressing presented in Pakistani dramas influences Islamic civilization and culture, promotes Western dress and western dress culture, and cause Islamic and social problems within a society. The researchers use the purposive sampling technique and collect data from 240 male and female respondents under cultivation theory. The researchers use the quantitative method, collect data through survey, The study’s demographic findings reveal that most unmarried female student respondent’s aged18-30 participated in the survey. Findings show that Pakistani TV dramas promote Western dressing culture, which is against the preaching’s of Islam. The majority of the respondents believe that Pakistani TV drama is not reflecting the Islamic civilization, culture, and dressing patterns shown in Pakistani TV drama are a hurdle to perform Islamic and religious worship. Pakistani TV drama strongly influences Pakistani people’s Islamic and social practices due to Western dressing, lifestyle, luxurious life, and Hindu religious activities.